Scarcity in the age of abundance:paradox and remedies - Rafikov, Ildus; Akhmetova, Elmira (Emerald Group Publishing Ltd., 2019)
Purpose This paper aims to examine the concepts of scarcity and abundance from an interdisciplinary perspective. It argues that the idea of economics, as the study of human behavior with regard to scarce resources and unlimited wants, leads to competition, confrontation and conflict, whereas the nature of humans is that of kindness, cooperation and sharing.